Kemampuan Representasi Matematis Ditinjau dari Gaya Belajar Siswa - Rezkyanti; Sitti Rahma Tahir; Nursakiah, Nursakiah; Ilhamsyah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
This study aims to describe mathematical representation ability in terms of students' learning styles. The type of research used is qualitative research with a descriptive approach. The subjects in this study were VIII grade students of SMP Negeri 1 Bontonompo as many as 3 students, namely 1 student of visual learning style, 1 student of auditorial learning style and 1 student of kinesthetic learning style. The instruments used were questionnaires, mathematical representation ability test sheets, and interview guidelines. The mathematical representation problem used was 1 problem which contained image representation, symbol representation and verbal representation. The results showed that: (1) subjects with visual learning styles have mathematical representation skills by fulfilling two aspects, namely symbol representation and verbal representation. (2) subjects with auditorial learning style have mathematical representation ability by fulfilling all aspects, namely symbol representation, verbal representation and image representation. (3) subjects with kinesthetic learning style have mathematical representation ability by fulfilling two aspects namely symbol representation and verbal representation.